Groundwater Classification by Using Fourier Analysis - A. Khalil, Mohamed (Global Journal of Earth Science and Engineering, 2022)
The article illustrates a statistical technique for the visual representation of geochemical data. Quaternary and Pre-Quaternary groundwater samples from Northern Sinai Peninsula, Egypt, were interpreted statistically using Andrews plots, which use Fourier analysis to transform and represent a set of multivariate data by a waveform pattern. The resulting waveform patterns were classified into low, middle, and high amplitudes, following up the increase in the total dissolved solids of the samples. Comparison with the traditional hydrochemical polygonal Stiff diagrams resulted in a complete matching. The proposed mixing between the Quaternary and Pre-Quaternary aquifers has been proved via the similarity of waveform patterns of the mixed water. The application of Andrews plots is investigated by comparison with the Stiff conventional diagrams. The correlation between different amplitudes and the TDS value of every sample indicates that the amplitude increases with the increase in the salinity.